Directed functional connectivity of the default-mode-network of young and older healthy subjects - Goelman, Gadi; Dan, Rotem; Bezdicek, Ondrej; Jech, Robert; Ekstein, Dana (Scientific reports, 2024)
Alterations in the default mode network (DMN) are associated with aging. We assessed age-dependent changes of DMN interactions and correlations with a battery of neuropsychological tests, to understand the differences of DMN directed connectivity between young and older subjects. Using a novel multivariate analysis method on resting-state functional MRI data from fifty young and thirty-one healthy older subjects, we calculated intra- and inter-DMN 4-nodes directed pathways. For the old subject group, we calculated the partial correlations of inter-DMN pathways with: psychomotor speed and working memory, executive function, language, long-term memory and visuospatial function. Pathways connecting the DMN with visual and limbic regions in older subjects engaged at BOLD low frequency and involved the dorsal posterior cingulate cortex (PCC), whereas in young subjects, they were at high frequency and involved the ventral PCC. Pathways combining the sensorimotor (SM) cortex and the DMN, were SM efferent in the young subjects and SM afferent in the older subjects. Most DMN efferent pathways correlated with reduced speed and working memory. We suggest that the reduced sensorimotor efferent and the increased need to control such activities, cause a higher dependency on external versus internal cues thus suggesting how physical activity might slow aging.
Keywords: mapování mozku; Aging; Default mode network; magnetická rezonanční tomografie; Brain; krátkodobá paměť; Multivariate analysis; Aged; Neural Pathways; senioři; Neuropsychological tests; Brain Mapping; lidé; Humans; stárnutí; nervové dráhy; mozek; zdraví dobrovolníci pro lékařské studie; Magnetic Resonance Imaging; Memory, Short-Term; Healthy Volunteers; Directed functional connectivity MRI